Hydrothermal analysis of MHD nanofluid (TiO2-GO) flow between two radiative stretchable rotating disks using AGM. (September 2019) - Zangooee, M.R.; Hosseinzadeh, Kh.; Ganji, D.D.
Abstract: Nanofluid flow between two stretchable and rotating disks with homogeneous and heterogeneous reactions and Joule heating is investigated in existence of magnetic field. Thermal radiation effect has been considered in energy equation. AGM Method is selected for solving ODEs. The effects of stretching parameters and Reynolds number on the concentration, temperature, axial, radial and tangential velocities are studied. The results showed that with increment of the values of stretching rate of lower disk, the radial and axial velocities enhances near the lower disk. Also the concentration and temperature is increasing behavior with stretching rate of lower disk. The impact of the increase of value of stretching rate of upper disk is opposite of the lower disk on the axial, radial and tangential velocities. The influence of Reynolds number on concentration, temperature and velocities are studied. It is shown that concentration is a decreasing function of Re while temperature is an increasing one. Also it is described that Nusselt number enhances with stretching parameter and Reynolds number at upper disk while it is decreased at lower one.